Communication traits among male adolescents in urban constituencies: A focus on the Namibian capital city of Windhoek (Namibian Journal of Linguistics, Literature and Communication Studies, 2026)
Male adolescents endure complex transitions from childhood. Our study explores the interpersonal and nonverbal communication traits of a sample of male adolescents in two urban constituencies of Windhoek, the capital city of the southern African nation of Namibia. The permutations of the research subjects’ lived experiences are canvassed through structured focus group discussions as well as administered questionnaires. In both data collection arrangements, the researchers sought to converse with and listen carefully to the target population. Windhoek East had 1175 adolescents and Windhoek West 4838. The research tools used to collect data for this study were a questionnaire and two focus group discussions. The study sought to explore the perception that male adolescents find it difficult to express themselves while dealing with life’s challenges, but may convey nonverbal cues, intentionally or unintentionally, about their state of mind. The intuition behind the research was that what male adolescents do and say may or may not reflect how they feel. The study’s objectives are twofold: to provide parents, social workers, and other stakeholders with insight into the challenges affecting male adolescents, their communication and behaviour, and to enhance scholarly understanding of how nonverbal cues might shape adolescent male responses.
Keywords: Adolescence; Interpersonal Communication; Nonverbal Communication; Namibia